Space and Spatiality in Modern German-Jewish History. - Lässig, Simone 1964- (New German Historical Perspectives Ser., 2017)
Intro -- Space and Spatiality in Modern German-Jewish History -- Contents -- Illustrations -- Preface -- Introduction: What Made a Space "Jewish"? Reconsidering a Category of Modern German History -- Part I - Imaginations: Remembrance and Representation of Spaces and Boundaries -- Chapter 1 - Of Sounds and Stones: The Jewish-Christian Contact Zone of a Swiss Village in the Nineteenth Century -- Chapter 2 - Imaginations of the Ghetto: Jewish Debates on Ghettos and Jewish Society in Late Nineteenth-Century Galicia -- Chapter 3 - Modernization and Memory in German-Jewish History -- Chapter 4 - From Place to Race and Back Again: The Jewishness of Psychoanalysis Revisited -- Chapter 5 - Jewish Displacement and Simulation in the German Films of E. A. Dupont -- Chapter 6 - Layered Pasts: The Judengasse in Frankfurt and Narrating German-Jewish History after the Holocaust -- Part II - Transformations: Emergences, Shifts, and Dissolutions in Spaces and Boundaries -- Chapter 7 - The Representation and Creation of Spaces through Print Media: Some Insights from the History of the Jewish Press -- Chapter 8 - Out of the Ghetto, Into the Middle Class: Changing Perspectives on Jewish Spaces in Nineteenth-Century Germany-The Case of Synagogues and Jewish Burial Grounds -- Chapter 9 - Spatial Variations and Locations: Synagogues at the Intersection of Architecture, Town, and Imagination -- Chapter 10 - Jewish Philanthropy and the Formation of Modernity: Baron de Hirsch and His Vision of Jewish Spaces in European Societies -- Chapter 11 - Reconstructing Jewishness, Deconstructing the Past: Reading Berlin's Scheunenviertel over the Course of the Twentieth Century -- Part III - Practices: Negotiating, Experiencing, and Appropriating Spaces and Boundaries -- Chapter 12 - A Hybrid Space of Knowledge and Communication: Hebrew Printing in Jessnitz, 1718-1745.